2011
DOI: 10.1016/j.jus.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasoundelastography: Can it provide valid information for differentiation of benign and malignant thyroid nodules?

Abstract: KEYWORDSThyroid; Thyroid sonography; Thyroid nodules; Sonoelastography; FNAC.Abstract Ultrasoundelastography (USE) is a new imaging technique that is performed with a normal ultrasound transducer. It provides improved characterization of a tissue or nodule based on the latter's elasticity and stiffness. The aim of the present, prospective study was to assess the validity of USE in characterizing thyroid nodules. USE patterns were analyzed in light of nodule cytology (British Thyroid Association classification)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…This literature review relied on the authors’ methodology as published in the relevant articles. Of the 25 studies, 22 indicated whether or not ROSE was undertaken. If ROSE was not specifically mentioned in the methods section or elsewhere in the article it was assumed that ROSE was not undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…This literature review relied on the authors’ methodology as published in the relevant articles. Of the 25 studies, 22 indicated whether or not ROSE was undertaken. If ROSE was not specifically mentioned in the methods section or elsewhere in the article it was assumed that ROSE was not undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Elastography, a noninvasive technique, has been introduced to evaluate the texture of the tissue and is useful in differentiating benign and malignant thyroid nodules 26 27 28 29 . Moon et al 21 also reported that a hard malignancy (Rago scores of 4–5) was an independent factor for predicting pathologic extrathyroidal extension on pathology, but was not a factor for predicting central and lateral lymph node metastasis on pathology of patients with PTMC.…”
Section: Discussionmentioning
confidence: 99%
“…La ecografía es fundamentalen la detección de nódulos, como apoyo en la obtención de muestras para estudio citopatológico, estadificación preoperatoria y seguimiento post operatorio (3). Los nódulos tiroideos pueden mostrar un patrón ecográfico muy diverso que muchas veces dificulta una segura catalogación con respecto a su malignidad (4). La elevada frecuencia de la ENT y la representatividad de los nódulos coloideos (particularmente los quísticos) constituyen argumentos para justificar esta investigación.…”
Section: Introductionunclassified